ปัจจัยที่มีอิทธิพลต่อการท่องเที่ยวเชิงส่งเสริมสุขภาพสำหรับชาวต่างชาติที่มา ท่องเที่ยวในประเทศไทย;FACTORS INFLUENCING HEALTH TOURISM AMONG FOREIGN VISITORS TO THAILAND : A PROMOTIONAL MODEL. - เลิศลัคธนาธาร, สิริกร; อ่อนมั่ง, ไพบูลย์; ลิบลับ, ไอยเรศ (Academic Journal Phranakhon Rajabhat University, 2017)
บทคัดย่อ การวิจัยในครั้งนี้มีวัตถุประสงค์เพื่อตรวจสอบความสอดคล้องของรูปแบบการท่องเที่ยวเชิงส่งเสริมสุขภาพสำหรับชาวต่างชาติที่มาท่องเที่ยวในประเทศไทยกับข้อมูลเชิงประจักษ์ซึ่งเป็นจำนวนประชากรนักท่องเที่ยวในปี พ.ศ.2556 จำนวน 26,735,583คน จะได้ขนาดกลุ่มตัวอย่างที่ระดับความเชื่อมั่น 95% และความผิดพลาดไม่เกิน 5% เท่ากับ 400 คน วิธีการสุ่มตัวอย่างคือการสุ่มตัวอย่างตามสะดวก เครื่องมือที่ใช้ในการวิจัยคือแบบสอบถาม สถิติที่ใช้ในการวิเคราะห์ข้อมูลคือสถิติพรรณนา ได้แก่ ค่าความถี่ ร้อยละ ค่าเฉลี่ยเลขคณิต ส่วนเบี่ยงเบนมาตรฐาน สถิติทดสอบสมมุติฐานประกอบด้วยสถิติวิเคราะห์เส้นทางอิทธิพลและสถิติวิเคราะห์โมเดลสมการเชิงโครงสร้าง (SEM) จากผลการทดสอบองค์ประกอบยืนยันแบบจำลองโครงสร้าง พบว่า จากการวิเคราะห์องค์ประกอบเชิงยืนยัน โมเดลการวิเคราะห์มีความสอดคล้องกับข้อมูลเชิงประจักษ์ ซึ่งประกอบด้วย 9 ปัจจัยหลักที่มีความเหมาะสม มีความเชื่อมั่น ความตรงเชิงโครงสร้างและเนื้อหาต่อรูปแบบการท่องเที่ยวเชิงส่งเสริมสุขภาพ Abstract The purpose of this researchwere to studyexamine validity of the modelof patterns of tourism among foreign visitors to Thailand : A promotional model. ThemultipleaspectsofEscapismthroughHealth Promotion Tourism primarily attract foreign visitor for their destinations.Thenpopulation wasforeign tourists sample size 400 sampling method convenience sampling theresearch instruments were questionnairesdistributed400people.In thefinalstagequestionnaireswerecollectedfromrespondents.Dataanalysisanddescriptivestatisticanalysedquantitative.The statistics used in data analysis by percentages, frequency, mean and standard deviation, the path analysis was used to test the hypothesis andmethodsof structural relationship models. Firstly, thedata werestatistically analysed by confirmatory factoranalysis. Nextbystructuralmodelsthe factorswere ratedin termsoftheirinfluenceon thedevelopmentmodelofhealthpromotiontourismforforeigntouristsincaseofstudyin Thailand.The results were as follows : that the model level had high construct validity. The model comprises of 9 factors SIGX, SPAX, SPEX, SERX, SPIX, SPOX, SPRX, STEX and SUSXand 25 sub-factors. As the result, The confirmatory factor analysis the measurement model is valid and well fitted to empirical data. The fitness values for the basic overall model all met the standard criterions, thus achieving desired levels. This model exhibits accept able level of fit. And used to confirm that all the factors are appropriate, construct validity and content validity the level is acceptable.